Both Monoclonal and Polyclonal Immunoglobulin Contingents Mediate Complement Activation in Monoclonal Gammopathy Associated-C3 Glomerulopathy - Chauvet, Sophie; Roumenina, Lubka T.; Aucouturier, Pierre; Marinozzi, Maria-Chiara; Dragon-Durey, Marie-Agnès; Karras, Alexandre; Delmas, Yahsou; Le Quintrec, Moglie; Guerrot, Dominique; Jourde-Chiche, Noémie; Ribes, David; Ronco, Pierre; et al. (Frontiers in Immunology, 2018)
C3 glomerulopathy (C3G) results from acquired or genetic abnormalities in the complement alternative pathway (AP). C3G with monoclonal immunoglobulin (MIg-C3G) was recently included in the spectrum of “monoclonal gammopathy of renal significance”. However, mechanisms of complement dysregulation in MIg-C3G are not described and the pathogenic effect of the monoclonal immunoglobulin is not understood. The purpose of this study was to investigate the mechanisms of complement dysregulation in a cohort of 41 patients with MIg-C3G. Low C3 level and elevated sC5b-9, both biomarkers of C3 and C5 convertase activation, were present in 44% and 78% of patients respectively. Rare pathogenic variants were identified in 2/28 (7%) tested patients suggesting that the disease is acquired in a large majority of patients. Anti-complement auto-antibodies were found in 20/41 (49%) patients, including anti-FH (17%), anti-CR1 (27%), anti-FI (5%) auto-antibodies, and C3 Nephritic Factor (7%) and were polyclonal in 77% of patients. Using cofactor assay, the regulation of the AP was altered in presence of purified IgG from 3/9 and 4/7 patients with anti-FH or anti-CR1 antibodies respectively. By using fluid and solid phase AP activation, we showed that total purified IgG of 22/34 (65%) MIg-C3G patients were able to enhance C3 convertase activity. In five documented cases, we showed that the C3 convertase enhancement was mostly due to the monoclonal immunoglobulin, thus paving the way for a new mechanism of complement dysregulation in C3G. All together the results highlight the contribution of both polyclonal and monoclonal Ig in MIg-C3G. They provide direct insights to treatment approaches and opened up a potential way to a personalized therapeutic strategy based on chemotherapy adapted to the B cell clone or immunosuppressive therapy